ASSESSMENT OF THE EFFECTIVENESS OF THE EFFECT OF PHYSICAL THERAPY ON THE DYNAMICS OF ASTHENO-DEPRESSIVE MANIFESTATIONS IN WOMEN AFTER ABDOMINAL DELIVERY - Grygus, I. M. (Rehabilitation and Recreation, 2023)
Purpose: Resume. Purpose: to determine the effectiveness of physical therapy in women after abdominal delivery according to the dynamics of astheno-depressive manifestations. Material. 45 women aged 23.7±1.2 years, in the late postpartum period after abdominal delivery (caesarean section) were examined. The comparison group consisted of 23 women who recovered during the postpartum period on their own, according to general recommendations. The main group consisted of 22 women who during the late postpartum period (1.5 months) underwent a physical therapy program (classes using breathing exercises and yoga exercises, Pilates exercises for the muscles of the back, abdomen, upper and lower limbs, therapeutic exercises for general strengthening body, increasing strength, flexibility, endurance; general massage; autogenic training sessions according to Schultz). The condition of women was evaluated according to the results of the Edinburgh Postnatal Depression Scale, Fatigue Assessment Scale, Fatigue Severity Scale, Epworth sleepiness scale. Results. During the initial examination, signs of depressive disorders, increased fatigue, and severe drowsiness were found in all women after cesarean section. During the re-examination, the women of the main group showed a statistically significantly better result (p<0.05) compared to the initial parameters for all the studied parameters: according to the Edinburgh Postnatal Depression Scale – by 42.6%, Fatigue Assessment Scale – by 51.8%, Fatigue Severity Scale – by 36.2%, Epworth sleepiness scale – by 45.2%, which can be associated with the reduction of physical weakness due to the use of the physical therapy program, as well as the direct positive effect of physical activity on the psycho-emotional state. All results were statistically significantly (p<0.05) better than the corresponding parameters of women in the comparison group who recovered independently (22.1%, 28.7%, 15.4%, 42.5%, respectively). Conclusions. Taking into account the etiopathogenesis and clinical course of postpartum depressive states, which, in particular, include an asthenic component, the use of physical therapy is justified in the process of recovery of women in the postpartum period after abdominal delivery to improve their psycho- emotional state, reduce the feeling of fatigue and weakness, and reduce drowsiness.